Simulation Analysis of Arc-Quenching Performance of Eco-Friendly Insulating Gas Mixture of CF3I and CO2 under Impulse Arc - Dong Wu; Wengui Chen; Zelin Ji (Journal of Electrical and Computer Engineering)
Due to its superior insulating qualities, SF6 gas is extensively used in the power sector. However, because of its poor environmental protection properties, finding ecologically acceptable insulating gas has become a critical challenge in the power sector in the context of pursuing green electricity. This work simulates the arc-quenching performance of a gas mixture of CF3I and CO2, which is thought to be a workable substitute for SF6 gas. The COMSOL software is used to build a two-dimensional model of a single-pipe arc-quenching chamber based on the concepts of magnetohydrodynamics (MHD) theory. The lightning impulse current is made by applying electrical stimulation to pure CO2 gas, gas mixtures with 10% CF3I and 90% CO2, and gas mixtures with 30% CF3I and 70% CO2 in the single-pipe arc-quenching chamber. During the first stage of arc formation, the results show that CF3I/CO2 gas mixtures with 10% and 30% CF3I have lower electrical conductivity than pure CO2 gas. An 8/20 μs lightning impulse current waveform with a magnitude of 4 kA is used for this observation. The highest airflow velocity for pure CO2 is 1744 m/s, but the mixture of 10%/90% CF3I/CO2 has a maximum airflow velocity of 1593 m/s. The 30%/70% CF3I/CO2 mixture has the highest maximum airflow velocity at 1840 m/s. Airflow velocity increases and the overpressure in the arc-quenching chamber is prolonged when there is a greater concentration of CF3I gas in the gas mixture. Consequently, these factors greatly reduce the duration of the arc-extinguishing time. The arc-quenching chamber’s overpressure is extended when the amount of CF3I gas in the gas mixture is increased, which increases the velocity of the airflow. As a result, these factors significantly decrease the duration of the arc-extinguishing time.